Detection of the dominant pathogens in diarrheal calves of Ningxia, China in 2021–2022 - Wang, Dong; Gao, Haihui; Zhao, Long; Lv, Changrong; Dou, Wei; Zhang, Xiuping; Liu, Yong; Kang, Xiaodong; Guo, Kangkang (Frontiers in Veterinary Science, 2023)
Introduction Calf diarrhea is a complex disease that has long been an unsolved problem in the cattle industry. Ningxia is at the forefront of China in the scale of cattle breeding, and calf diarrhea gravely restricts the development of Ningxia's cattle industry. Methods From July 2021 to May 2022, we collected diarrhea stool samples from calves aged 1–103 days from 23 farms in five cities in Ningxia, and performed PCR using specific primers for 15 major reported pathogens of calf diarrhea, including bacteria, viruses, and parasites. The effect of different seasons on the occurrence of diarrhea in calves was explored, the respective epidemic pathogens in different seasons were screened, and more detailed epidemiological investigations were carried out in Yinchuan and Wuzhong. In addition, we analyzed the relationship between different ages, river distributions and pathogen prevalence. Results Eventually, 10 pathogens were detected, of which 9 pathogens were pathogenic and 1 pathogen was non-pathogenic. The pathogens with the highest detection rate were Cryptosporidium (50.46%), Bovine rotavirus (BRV) (23.18%), Escherichia coli (E. coli) K99 (20.00%), and Bovine coronavirus (BCoV) (11.82%). The remaining pathogens such as Coccidia (6.90%), Bovine Astrovirus (BoAstV) (5.46%), Bovine Torovirus (BToV) (4.09%), and Bovine Kobuvirus (BKoV) (3.18%) primarily existed in the form of mixed infection. Discussion The analysis showed that different cities in Ningxia have different pathogens responsible for diarrhea, with Cryptosporidium and BRV being the most important pathogens responsible for diarrhea in calves in all cities. Control measures against those pathogens should be enforced to effectively prevent diarrhea in calves in China.